Georgia Architectural and Historic Properties Survey of Rural [294] Unknown, Valdosta, Ga. December 1980. - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [294] Unknown, Valdosta, Ga. December 1980. A one story rectangular plan with gabled tin roof and clapboard siding. Shed porch (screened) with turned spindle posts. Sash windows with 2/2 lights. Exterior chimney. Brick piers. Fair condition. Double front doors. Date of Construction: c. 1910. A typical rural vernacular house common to these rural areas.
Georgia Architectural and Historic Properties Survey of Rural [294] Unknown, Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 864 KB (885,645 bytes).
Keywords: Valdosta (Ga.); Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.)